2022
DOI: 10.1016/j.optom.2020.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting factors for progression of the myopia in the MiSight assessment study Spain (MASS)

Abstract: Purpose To investigate which baseline factors are predictive for success in controlling myopia progression in a group of children wearing MiSight Contact Lens (CLs). Methods Myopic patients (n = 41) fitted with MiSight CLs and followed up two years were included in this study. Bivariate analysis, a logistic regression analysis (LG) and a decision tree (DT) approach were used to screen for the factors influencing the success of the treatment. To assess the response, axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Additionally, excessive AL growth is associated with future pathology. Prieto‐Garrido et al 7 defined “responders” to dual‐focus soft contact lens treatment as those with an AL increase of <0.11 mm per year. In the present study, the increase in AL during the 12‐month period in the dual‐focus soft contact lens group was 0.13 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, excessive AL growth is associated with future pathology. Prieto‐Garrido et al 7 defined “responders” to dual‐focus soft contact lens treatment as those with an AL increase of <0.11 mm per year. In the present study, the increase in AL during the 12‐month period in the dual‐focus soft contact lens group was 0.13 mm.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report proposed that time spent outdoors was the main factor in controlling myopia progression in children using dual-focus soft contact lenses. 7 The association between time spent outdoors and myopia onset is now well established, 11,12 with the most plausible explanation being the increase in dopamine production following sunlight exposure. 13 However, the role of outdoor light exposure and myopia progression remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent intervention studies designed to slow myopia progression have labelled participants who showed a pattern of fast progression during treatment as non-responders. [1][2][3][4][5] However, we caution against using the terms 'non-responder' and 'fast progressor' interchangeably. The progression of myopia across childhood is often characterised by spurts of fast eye growth interspersed with slower phases.…”
Section: Identifying Non-responders To Treatments For Myopiamentioning
confidence: 99%
“…MiSight's daily lens product was FDA-approved in 2019 for SCLs that slow myopia in children while correcting vision using a concentric ring design. [376,377] According to the NIH, the clinical approval period for this SCL was six years. Another SCL device on the market is the SENSIMED Triggerfish®, which performs intraocular pressure sensing and received FDA approval in 2017.…”
Section: Challenges Of Smart Contact Lensesmentioning
confidence: 99%